CLAUSA Is a MYB Transcription Factor That Promotes Leaf Differentiation by Attenuating Cytokinin Signaling. Issue 7 (6th July 2016) - Bar, Maya; Israeli, Alon; Levy, Matan; Ben Gera, Hadas; Jiménez-Gómez, José M.; Kouril, Stepan; Tarkowski, Petr; Ori, Naomi
Abstract : The tomato CLAUSA gene encodes a unique MYB transcription factor that promotes leaf differentiation by attenuating cytokinin response. Abstract: Leaf morphogenesis and differentiation are highly flexible processes, resulting in a large diversity of leaf forms. The development of compound leaves involves an extended morphogenesis stage compared with that of simple leaves, and the tomato ( Solanum lycopersicum ) mutant clausa ( clau ) exposes a potential for extended morphogenesis in tomato leaves. Here, we report that the CLAU gene encodes a MYB transcription factor that has evolved a unique role in compound-leaf species to promote an exit from the morphogenetic phase of tomato leaf development. We show that CLAU attenuates cytokinin signaling, and that clau plants have increased cytokinin sensitivity. The results suggest that flexible leaf patterning involves a coordinated interplay between transcription factors and hormones.